A review of the genus Discomyza (Diptera: Ephydridae) from Afrotropical, Australasian/Oceanian and Oriental Regions - Zatwarnicki, Tadeusz; Cielniak, Magdalena (Zootaxa, 2015)
Tropical Old World species of the genus Discomyza are redescribed, including male terminalia, photographs of heads and wings. One new species Discomyza fagomoga sp. nov. is described from D. R. Congo, Ethiopia, Kenya and Uganda. Two new synonyms are proposed: Discomyza obscuricornis Canzoneri and Rampini, 1996 = D. dolichocerus Cresson, 1944 and D. intermedia Canzoneri and Meneghini, 1969 = D. eritrea Cresson, 1939. A key to all species is provided. Relationships among species of Discomyza are suggested.